Risk factors, prevention and control strategies for surgical site infections in veterinary practice in Nigeria: A review (2016)
Surgical site infections (SSIs) are surgery associated nosocomial infections with multifactorial etiologies. They are adverse events that have placed heavy burden on surgery universally and have bedeviled veterinary surgery practice in Nigeria for decades, with consequent severe morbidity, mortality, financial and psychological burden on animal owners. In this paper, information on current universal trend of SSIs, including risk factors, prevention and control strategies was reviewed with emphasis on principles and practice among small animals and equine surgery practitioners. Principles guiding surgical suite design, surgical team, instruments/equipment, and patient preparation, were emphasized. It was concluded that imbibing the principles and practice of SSIs prevention strategies in Nigeria veterinary hospitals and clinics would impact positively on the veterinary health care system and the society the Veterinarian is committed to serve